A influência do professor artista no ensino das artes - Pola, Cláudia, 1969- (2015)
The contemporary world presents us with a plethora of views. We are ready for dialogue and diversity? What action will the mediator artist teacher in the teaching of Visual Arts with this filing? Find that teacher artist rationale in human history, in the history of Art, in pedagogical theories, on their own experiences in educational systems in which they operate in space and connections for knowledge sharing, sufficient foundation that assist in its mission to teacher influential artist? This range of questions and the challenge of teaching and learning and learning to teach prompted us to carry out this research work on "the influence that teacher artist is in the teaches of Arts in Brazil." The aim is to deepen the framework of knowledge on pedagogical theories, evaluating them through various practices Brazilian teachers collected through collective case study methodology. To do this we used a tool called narrative interview. With these narratives, in comparison with the literature review, we proceed to its content analysis. Some final considerations are earned for the teacher to artist can play with excellence seconds Ralph Smith revealed in their studies, however Richard Sennett opposed this demand for excellence that blocks more open paths, and respond more pre preconceived ideas than to tears of creativity desirable in courses where are explored possibilities and not exclusionary truths, this search for excellence in the sense of the author can sell as the ideal there is very little such as the welcome given to the class, competence in content knowledge, methods and teaching techniques . However, it is urgent also from the analyzes, draw new questions that challenge teachers, school systems and the entire global society, projecting ways of understanding the visual experience their contexts, the implications for mediation meaningful learning. Therefore, it is also a function of researchers to search for answers that cause other forms of questioning and inquiry promoting the discovery of new learning spaces that face contemporary challenges. Arts teachers, from their diverse experiences required transdisciplinary approach, constitute a valuable contribution to the promotion of a significant understanding of the society and the confrontation and mirror processes that offer us the artistic narratives and visual production that emulsify our educational and social experience. We realize that all teachers are always looking for an ideal and this ideal can be applied by the artists teachers because the aesthetic experience that were acquired with time and also during the interviews evidenced the importance of new knowledge and discoveries, as the influence of significant Professor artist who is plugged into the present, attentive to new discoveries and open to new perspectives. Therefore the fixed knowledge better when we have an aesthetic experience and it is this experience that expands the new knowledge and innovation can enable the artistic learning in the visual arts education. However it is extremely important value teachers artist who develops a parallel activity to education, for the more artistic references teachers acquire and reaffirm can offer better success with his teaching in the arts